2020
DOI: 10.52690/jadila.v1i1.13
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Speaking Anxiety in English Class

Abstract: This research aimed to find out the level of students’ speaking anxiety students in English class and the most dominant factors that caused students’ speaking anxiety faced by the third grade students of Junior High School in SMPN 15 Bengkulu in English Classroom. This research used descriptive quantitative design with questionnaire as the instrument. The questionnaire of this research was Foreign Language Classroom Anxiety Scale (FLCAS) proposed by Horwitz et al. (1983). The data has been analyzed by using SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…To understand the phenomenon that occurs in ESP class, the researcher believed the qualitative approach was to solve speaking issues at UNISBA Blitar and it was very useful for the researcher to get a better insight into speaking anxiety in ESP Class. Sinaga et al's (2020) study emphasized that speaking anxiety to students at UNISBA Blitar was a natural phenomenon. The characteristic of this approach would unveil the factors of speaking anxiety as a natural phenomenon and it would answer the other research problems.…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations
“…To understand the phenomenon that occurs in ESP class, the researcher believed the qualitative approach was to solve speaking issues at UNISBA Blitar and it was very useful for the researcher to get a better insight into speaking anxiety in ESP Class. Sinaga et al's (2020) study emphasized that speaking anxiety to students at UNISBA Blitar was a natural phenomenon. The characteristic of this approach would unveil the factors of speaking anxiety as a natural phenomenon and it would answer the other research problems.…”
Section: Methodsmentioning
confidence: 96%
“…The students (ESP class) at UNISBA Blitar need a creative lecturer because English speaking can be a stressful activity. Speaking English may be a problematic practice since it is not used as the primary language of speech (Sinaga et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The questionnaire results were classified into five levels of anxiety, namely: very anxious, anxious, mildly anxious, relaxed, and very relaxed (Sinaga et al, 2020). The distribution of anxiety levels is presented in Table 4.2: The result showed that the majority of students (each 32 or 46.4%) perceived mildly anxious and relaxed in their speaking class.…”
Section: Students' Perceived Anxietymentioning
confidence: 99%